Apparent Communications from an Eager Spirit - Targ, Russell (Journal of Scientific Exploration, 2017)
My daughter, psychiatrist Elisabeth Targ, a pioneer in the field of mind/body medical research, died July 18th, 2002 of a brain tumor at the age of 40. She was recognized as a brilliant researcher, graduating from Stanford University at nineteen, with a degree in biology and a Russian Translators certificate. She then went on to do original research in distant healing at California Pacific Medical Center. In a double blind study with her 60 AIDS patients, those who received distant healing had significantly better outcomes, fewer trips to the hospital, fewer days in the hospital, better self-report, etc., than the controls for whom no prayers were said, (Western Medical Journal, Dec.1998). Elisabeth died in the living room of my home in Portola Valley, California, overlooking Stanford and San Francisco Bay to the east. That was her request. The following day, I sat with her husband Mark Comings and my friend Jane Katra, on a deck watching the lights of Palo Alto begin to come on through the fog. We were wondering if we would ever hear from Elisabeth. Moments later, all the lights in the three-story house flashed off, leaving us in the semi-darkness. “What was that,” we all said at once. Could it be an answer to our question? At which the lights came on. A few seconds later the lights again flashed off and then on again. Such a thing never happened before or since in this five year old building.